Leitura compartilhada e promoção do letramento emergente de pré-escolares com deficiência intelectual - Conti, Lilian Maria Carminato (Universidade Federal de São Carlos, 2014)
Among the challenges of educational inclusion, it stands out to ensure children with intellectual disabilities effective conditions for the development of their learning to read potential. To provide opportunities since early childhood education, in order to make students have active contact with reading and writing, shows itself as a favoring factor of Emergent Literacy development, that is, the knowledge and abilities related to reading and writing increase the chances of the child to succeed on learning to decode and understanding texts. This study had as main objective to build, implement and to analyze an Emergent Literacy promotion program for preschool students with intellectual disabilities guided by a teaching approach characterized as shared reading. The study had as specific objectives: to obtain a characterization of students Emergent Literacy abilities, in order to support the planning of the interventions; to describe the activities and adaptations of the material used by teachers and students in shared reading situations, considering the sessions held; to describe students engagement in shared reading activities; to analyze the main activities developed by the researcher in shared reading context, focusing the development of the different components of Emergent Literacy, as much as the adaptations in face of the different characteristics of the students. The participants were two students with Down syndrome, aged 3 to 5 years old, that attended a municipal center of early childhood education. This is a descriptive and exploratory study, because it searches a better comprehension of a so far little studied phenomenon. The program was applied individually, and was conducted by the researcher responsible for the study. The shared reading sessions were filmed, in order to obtain the descriptions related to activities and adaptations made by the teacher, as well as descriptions of students engagement on the activities. Shared reading sessions were made, which proposed activities that could promote familiarity with Emergent Literacy components. The program results point that the participants had systematic opportunities to explore books, choose them independently, of observing and listening to the researcher read a wide range of stories, and of participating in activities that required the presentation of behaviors associated to different components of Emerging Literacy. The results referred to the engagement on the activities point that through the sessions occurred an increase of the interest by books and readings, of the participation during readings, of the comprehension of the stories, on the proper handle of the books, and on the use of concepts about reading and its functions. The participants had opportunities to be involved in make believe readings and recognizing this concept. It is discussed the possibilities of continuing the study in view of the importance of demonstrating possibilities that come of efficient approaches for the promotion of Emergent Literacy among students with intellectual disabilities, in order to guide teachers work on early childhood education context.
Shared reading and the promotion of Emergent Literacy among preschool students with intellectual disability
Keywords: Educação infantil; Leitura - ensino - aprendizagem; Letramento emergente; Leitura compartilhada; Deficiência intelectual; Pré-Escolares; Special education; Emergent literacy; Shared reading; Intellectual disability; Preschool students; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL